2022
DOI: 10.1002/jso.26799
|View full text |Cite
|
Sign up to set email alerts
|

Same‐day mastectomy and axillary lymph node dissection is safe for most patients with breast cancer

Abstract: Background and Objective The aim of this study was to evaluate the safety of same‐day mastectomy, with or without a sentinel node biopsy (SNB) and/or axillary lymph node dissection (ALND). Methods In this retrospective study, we reviewed 913 consecutive women who underwent a simple mastectomy for breast cancer between the years 2014 and 2019 and were treated either with same‐day surgery (SDS) or an overnight stay (OS) regime. We reviewed all surgical complications, any unplanned return to care (RTC) and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Many studies have confirmed that it is safe for breast cancer patients to be discharged within 24 h after mastectomy 21 , 43 46 , which were the same as our study. However, it is less feasible to discharge patients who have undergone implant-based breast reconstruction within 24 h at breast centres worldwide, let alone E-NSM with DIBR.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have confirmed that it is safe for breast cancer patients to be discharged within 24 h after mastectomy 21 , 43 46 , which were the same as our study. However, it is less feasible to discharge patients who have undergone implant-based breast reconstruction within 24 h at breast centres worldwide, let alone E-NSM with DIBR.…”
Section: Discussionsupporting
confidence: 89%
“…Initial consultation and molecular targeted therapy necessitate affirmative changes in the key genes of breast cancer progression, conversion, and poor prognosis. The manifestations of VEGF and FAM83A correspond significantly to the various clinical pathological characteristics and prognosis of breast cancer patients and can be regarded as the therapeutic target of breast cancer [ 14 ]. Studies in the literature suggest that some molecular markers are associated with poor prognosis in breast cancer; for example, the human-encoded FAM83A gene is highly expressed in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that patients discharged on the day of MwoR have equivalent surgical outcomes (e.g., complications, reoperations, emergency room visits) with improved patient-reported outcomes (e.g., satisfaction with care) than patients admitted for 1 or more nights, controlling for patient demographics and comorbidities. 9 12 There are also data suggesting that differences in surgeon practice patterns, rather than differences in patient demographics or comorbidities, may be driving this practice. 13 Moreover, a review article by the American Society of Breast Surgeons was recently released describing important factors to consider when starting a same-day mastectomy program.…”
mentioning
confidence: 99%